"A perspective close to our own": footsteps travel and the Japanese reception of Isabella Bird's Unbeaten Tracks in Japan, 1996–2016. Issue 1 (2nd January 2017) - Elliott, Andrew
ABSTRACT: While it was the 1973 Takanashi translation of Unbeaten Tracks that first brought popular attention to Isabella Bird in Japan, the two decades since the mid-1990s have seen a steady flow of books which either rewrite Unbeaten Tracks or retrace Bird's route through Tōhoku to Hokkaidō. This article analyses these footsteps travel texts in order to consider Bird's appeal and the socio-cultural function of Bird and Unbeaten Tracks in post-Bubble Japan. I argue that the "connection" that these texts create between past and present is sometimes understood individually, as cross-identification between the historical Bird and the contemporary traveller/writer, but more commonly in terms of family or national genealogy, a promise of unbroken transmission from the past designed to assuage anxieties about the loss of national-cultural cohesion and distinction. In many cases, these texts allow nostalgia to be transformed into celebration of national continuity; in other cases, however, this project of recovery is forestalled by the very unfamiliarity of Bird's perspective, which cannot help but reveal that, for modern Japanese readers, "the past is a foreign country".